2009
DOI: 10.1080/14767050902926947
|View full text |Cite
|
Sign up to set email alerts
|

Maternal hemoglobin concentration and its association with birth weight in newborns of mothers with preeclampsia

Abstract: OBJECTIVE Maternal hemoglobin concentration is inversely related to newborn size presumably through plasma volume constriction. We sought to determine whether birth weight would show an inverse relationship to hemoglobin concentration in a group of infants whose mothers had preeclampsia, where plasma volume constriction is common. METHODS Electronic and paper chart review identified 142 nulliparous women with preeclampsia (excluding HELLP syndrome). Birth weight percentile was determined based on cross-secti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
7
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 29 publications
2
7
0
1
Order By: Relevance
“…Placental dysfunction and increased inflammation are believed to underlie the pathogenesis of severe preeclampsia (PE), which may involve interleukin-induced signaling [54]. In addition, researches have shown that maternal hemoglobin concentrations are significantly changed prior to delivery in women with preeclampsia [55]. In this work, hemoglobin subunit zeta was found down regulated about 4.9 fold.…”
Section: Discussionmentioning
confidence: 70%
“…Placental dysfunction and increased inflammation are believed to underlie the pathogenesis of severe preeclampsia (PE), which may involve interleukin-induced signaling [54]. In addition, researches have shown that maternal hemoglobin concentrations are significantly changed prior to delivery in women with preeclampsia [55]. In this work, hemoglobin subunit zeta was found down regulated about 4.9 fold.…”
Section: Discussionmentioning
confidence: 70%
“…As we did not include pre‐eclampsia or maternal chronic conditions in this analysis, we cannot exclude their possible role in the development of asthma among offspring. However, pre‐eclampsia has been associated merely with high maternal hemoglobin levels during pregnancy . It is unlikely that pre‐eclampsia could explain the detected significant association between the risk of asthma among offspring and low maternal hemoglobin levels and anemia during pregnancy.…”
Section: Discussionmentioning
confidence: 98%
“…Hemoglobin level is higher in control group when we compare it with the patient group ( P < 0.001). A study showed that maternal z score of hemoglobin was significantly higher in pre‐eclampsia patients compared to controls …”
Section: Discussionmentioning
confidence: 99%